Analysis Of Plastic Pellets Production Process To Reduce Waste Using Lean Six Sigma Method And FMEA - Muhammad Hafiz Aziz; Dira Ernawati (Jurnal Sistem Cerdas, 2025)
The rapid development of the industry has increased plastic production to meet market demand, which has led to a rise in plastic waste volume. One way to reduce plastic waste is by processing it into plastic pellets. CV. XYZ is a company that produces plastic pellets from PP, PS, and PE waste in Gresik, East Java. In its production process, the company faces issues such as high lead times of 990 minutes and non-standard product quality, including defects like clumping, cutting failures, and broken plastic pellets. This study aims to reduce waste and minimize lead time by applying the lean six sigma method with a DMAIC and FMEA approach. Three dominant types of waste were identified: storage, defects, and transportation. The implementation of improvement proposals successfully reduced lead time from 990 minutes to 780 minutes. The average sigma level was recorded at 3.14 with a DPMO of 50009, which falls into the good category for the average industry in Indonesia. Recommendations include demand forecasting, operator training, supplier selection, improving raw material quality, material handling, and utilizing conveyors in certain areas while minimizing non-value-added activities. Through the design of process activity mapping and big picture mapping, the efficiency of plastic pellet production can increase from 50.51% to 64.10%